Application of sequential searching method in searching case data at the office Prosecutor's office - Fansyuri Nasution, Hamzah; Suranti, Dewi; Fredricka, Jhoanne (Jurnal Komputer Indonesia, 2023)
The case data management process handled by Bengkulu District Prosecutor's Office uses computers using office applications to create letters and tables of evidence for each case. The large amount of case data that comes in every day means that staff need quite a long time to make reports. Apart from that, the staff searched for data on cases that had occurred previously where there was a request from the head of the prosecutor's office, but this took quite a long time because the data that had been processed was already in the form of data archiving so that the staff had to manually search for the case data one by one. This reduces the effectiveness and efficiency of the performance of each staff member at Bengkulu District Prosecutor's Office. The application of the Sequential Searching Method in searching for case data at Bengkulu District Prosecutor's Office is a forum built to make it easier for staff at the office to manage case data and search for case data that has been entered. Apart from that, it can help staff in archiving data on cases that have been handled every month. To make it easier for staff to manage case data, a web-based application was built that can be accessed via a browser created using the PHP programming language and MySQL database.